Appreciation of the Indian rupee : a study in international monetary mechanism - Gowda, Venkatagiri K. (Allahabad : Chaitanya Pub. House, 1961)
In this book, the author compares the rupee-sterling relations a year after the Indian rupee area currencies were devalued in 1949, agitation was started in India for an appreciation of the rupee in order to combat internal inflation. It also attempt to distinguished by its analysis of the pros and cons of currency appreciation, and of exchange rate policies in India.
Includes bibliographical footnotes and index
usc 21/06/2018
Loans
Keywords: Exchange rates; Currency question; Money; Rupee, Indian; India